A Criterion Based Rehabilitation Protocol for ACL Repair with Internal Brace Augmentation - Ahmer Irfan; Stewart Kerr; Graeme Hopper; William Wilson; Lynsay Wilson; Gordon Mackay (North American Sports Medicine Institute, 2021)
The anterior cruciate ligament (ACL) is one of the main stabilizing structures of the knee and its rupture is a common injury in young active adults. ACL reconstruction has been the preferred operative management of an ACL rupture for several decades; however, success rates are variable. Recently, interest in arthroscopic primary repair of the ligament has increased. The repair is augmented with an Internal Brace (IB), which is an ultra-high strength suture tape that bridges the ligament. This technique protects the ligament during the healing and the ligament is encouraged to heal naturally, whilst not requiring any external braces. It acts as a stabiliser to permit early mobilization and optimise rehabilitation. As understanding of rehabilitation has progressed, there has been an increased focus on early weight-bearing and achieving full range of movement. While detailed criterion-based rehabilitation protocols exist for ACL reconstruction, this is not the case for ACL repair. The purpose of this commentary is to present a novel criterion-based rehabilitation protocol following ACL repair surgery augmented with an IB. # Level of Evidence V